2005
DOI: 10.1002/hep.20662
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced tyrosine nitration and inactivation of hepatic glutamine synthetase in the rat

Abstract: Glutamine synthetase (GS) in the liver is restricted to a small perivenous hepatocyte population and plays an important role in the scavenging of ammonia that has escaped the periportal urea-synthesizing compartment. We examined the effect of a single intraperitoneal injection of lipopolysaccharide (LPS) in vivo on glutamine synthesis in rat liver. LPS injection induced expression of inducible nitric oxide synthase, which was maximal after 6 to 12 hours but returned toward control levels within 24 hours. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 28 publications
6
75
0
Order By: Relevance
“…Liver injury can result in a reduction of hepatic GS activity (21,24). Because other potent ammonia detoxicating mechanisms exist in the body, the role of the GS in perivenous liver cells remains controversial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver injury can result in a reduction of hepatic GS activity (21,24). Because other potent ammonia detoxicating mechanisms exist in the body, the role of the GS in perivenous liver cells remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…For example, LPS-induced liver injury results in PTN of hepatic GS, which inactivates the enzyme (21). The impact of the urea cycle for ammonia metabolism can be seen in children with urea cycle defects, who exhibit hyperammonemia and cognitive symptoms (22).…”
mentioning
confidence: 99%
“…Hyperammonemia is observed in experimental rodent models of sepsis, such as cecal ligation and puncture [6] or LPS administration [7] suggesting defective hepatic ammonia detoxification. In fact, LPS has been demonstrated to inhibit hepatic glutamine synthesis through the inactivation of the glutamine synthetase [8]. Nevertheless, studies in isolated perfused livers from septic [25] or LPS-treated [8] rats showed a slightly or not affected ammonia metabolism via ureagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, LPS has been demonstrated to inhibit hepatic glutamine synthesis through the inactivation of the glutamine synthetase [8]. Nevertheless, studies in isolated perfused livers from septic [25] or LPS-treated [8] rats showed a slightly or not affected ammonia metabolism via ureagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation